European Citizens’ Initiative and the Democratic Deficit in Albanian Legislation: A Comprehensive Analysis - Nezha, Kelmend; Mucollari, Oriona (European Journal of Multidisciplinary Studies, 2019)
Democracy can take various forms, with participation and representation being crucial aspects of modern democracy. In a representative democracy such as the European Union (EU), representative democracy is expressed through elected institutions such as the European Parliament, while participatory democracy is embodied in the European Citizens’ Initiative (ECI) established in the Treaty of Lisbon. This revolutionary form of democracy, reformed within the EU, consists of participatory democracy, where the EU engages in creating and providing European citizens with the opportunity to submit a request to the European Commission for the drafting of new legislation in a specific field within its competence. Thus, the ECI becomes a new machine for policy-making in the EU, driven by ordinary citizens. In this way, European citizens are granted the direct right to have a say in the EU legislative process. However, the implementation of the ECI poses several challenges, including the need for sufficient awareness among citizens, the complexity of the procedure, and the potential mismatch between citizen demands and EU policy priorities. The aim of this paper is to analyze the implementation of the ECI as an integral part of the Treaty of Lisbon, particularly in relation to EU member states that have provided opportunities for citizen participation in their national legislations, including the provisions offered by the legislation of the Republic of Albania in this field.